2019
DOI: 10.1144/sp492-2017-329
|View full text |Cite
|
Sign up to set email alerts
|

The forensic application of ground-penetrating radar, Tekoha Jevy indigenous village, Paraná, Brazil

Abstract: Any archaeological site, according to the Brazilian Federal Constitution, is a patrimony of the Union; consequently, when crimes against this cultural patrimony occur, it becomes the responsibility of the Federal Police of Brazil. In 2013, there was a complaint to the Brazilian Federal Public Prosecutor's Office about the depredation of an archaeological site and forced withdrawal of the indigenous people because of the construction of a multimodal port in the city of Guaíra, in the state of Paraná, in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are known markers to help detect small‐scale artefacts and their fragments—diffracted wave hyperbolas generated by local features whose electrophysical properties are in contrast with the enclosing ground. For example, Canata et al (2019) demonstrated how distinct the ceramic items with 10 to 35 cm dimensions buried at depths down to 37 cm were in the GPR cross‐section obtained at 700 MHz frequency.…”
Section: Methodology and Survey Designmentioning
confidence: 99%
“…There are known markers to help detect small‐scale artefacts and their fragments—diffracted wave hyperbolas generated by local features whose electrophysical properties are in contrast with the enclosing ground. For example, Canata et al (2019) demonstrated how distinct the ceramic items with 10 to 35 cm dimensions buried at depths down to 37 cm were in the GPR cross‐section obtained at 700 MHz frequency.…”
Section: Methodology and Survey Designmentioning
confidence: 99%